2022
DOI: 10.3389/fsurg.2022.977505
|View full text |Cite
|
Sign up to set email alerts
|

An artificial neural network model based on standing lateral radiographs for predicting sitting pelvic tilt in healthy adults

Abstract: BackgroundSpinopelvic motion, the cornerstone of the sagittal balance of the human body, is pivotal in patient-specific total hip arthroplasty.PurposeThis study aims to develop a novel model using back propagation neural network (BPNN) to predict pelvic changes when one sits down, based on standing lateral spinopelvic radiographs.MethodsYoung healthy volunteers were included in the study, 18 spinopelvic parameters were taken, such as pelvic incidence (PI) and so on. First, standing parameters correlated with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We gathered radiographic data from the literature that presented normal spinal measurements [ 3 , [36] , [37] , [38] , 40 , 42 , [44] , [45] , [46] , [47] ]. Ten articles were found to publish sitting and standing radiographic measures with a total sample size of 1066 subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We gathered radiographic data from the literature that presented normal spinal measurements [ 3 , [36] , [37] , [38] , 40 , 42 , [44] , [45] , [46] , [47] ]. Ten articles were found to publish sitting and standing radiographic measures with a total sample size of 1066 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…When sitting in a natural position, a vague C shape is formed, which can significantly affect the values of various measures [ 18 ]. Two studies indicated the use of a natural sitting position [ 44 , 46 ], while the remaining indicated an erect sitting position [ 3 , [36] , [37] , [38] , 40 , 42 , 45 , 47 ]. This was not controlled for in our systematic review and should be a noted limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation